2000
DOI: 10.1902/jop.2000.71.10.1546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roxithromycin on Tumor Necrosis Factor‐Alpha‐Induced Vascular Endothelial Growth Factor Expression in Human Periodontal Ligament Cells in Culture

Abstract: These results indicate that TNF-alpha, one of the proinflammatory cytokines implicated in the pathogenesis of periodontitis, induces excess induction of VEGF in HPDL, which may account for increased angiogenesis in periodontitis lesions. Interestingly, the antibiotic roxithromycin inhibits TNF-mediated VEGF induction, suggesting its possible therapeutic utility in periodontitis and other chronic inflammatory conditions involving VEGF induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…Nitric oxide causes DNA breaks and enhances DNA mutations, especially in hepatitis C virus -associated hepatocellular carcinoma (27). Because cloning and functional analysis of the human iNOS gene promoter have identified several copies of NF-nB response elements and several copies of activator protein 1 binding sites, roxithromycin could affect the inactivation of iNOS, as reported in the present study and our former studies (9). Furthermore, iNOS and NADPH oxidase are major sources of reactive oxygen species in experimental hepatocarcinogenesis (28).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Nitric oxide causes DNA breaks and enhances DNA mutations, especially in hepatitis C virus -associated hepatocellular carcinoma (27). Because cloning and functional analysis of the human iNOS gene promoter have identified several copies of NF-nB response elements and several copies of activator protein 1 binding sites, roxithromycin could affect the inactivation of iNOS, as reported in the present study and our former studies (9). Furthermore, iNOS and NADPH oxidase are major sources of reactive oxygen species in experimental hepatocarcinogenesis (28).…”
Section: Discussionsupporting
confidence: 67%
“…Many researchers have shown that an important aspect of inflammation is extravasation of neutrophils into tissues (30 -32). Macrolides inhibit the production of many proinflammatory cytokines such as interleukin 1, interleukin 6, interleukin 8, and tumor necrosis factor a, perhaps by suppressing the transcription factor NF-nB or activator protein 1 (9). Inhibition of cytokine production has been observed in vitro and also in bronchoalveolar lavage fluid, which contains less interleukin 8 and fewer neutrophils after treatment with macrolides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascularization of tumors requires the release of angiogenic growth factors (eg VEGF, MCP-1) from tumor cells and/or inflammatory cells such as macrophages and neutrophils or in response to pro-inflammatory cytokines (eg TNF). [120][121][122] NF-B regulates the expression of such growth factors and cytokines (VEGF, TNF, MCP-1) necessary for angiogenesis providing another pathway for which inhibition of NF-B may be justified in anti-cancer therapy. [123][124][125][126] …”
Section: Role Of Nf-b In Angiogenesismentioning
confidence: 99%
“…The VEGF promoter contains AP-1, AP-2, SP-1, and HIF-1 binding sites [6,7]. Hypoxia induces VEGF expression through activation of HIF-1 [7] and AP-1 [8,9], whereas tumor necrosis factor (TNF)-a increases VEGF expression via SP-1 [8,10].…”
Section: Introductionmentioning
confidence: 99%